Analysis on Concentration and Source Rate of Precursor Vapors Participating in Particle Formation and Growth at Xinken in the Pearl River Delta of China - 龚有国 苏杭 程雅芳 刘峰 吴志军 胡敏 曾立民 张远航 (Advances in atmospheric sciences, 2008)
Concentration and source rate of precursor vapors participating in particle formation and subsequent growth were investigated during the Pearl River Delta intensive campaign （PRD2004, October 2004） in southeastern China. Four new particle formation event days and a typical non-event day were selected for our analysis. Atmospheric sulphuric acid, the important precursor vapor in nucleation and growth, were simulated with a pseudo steady-state model based on the measurements of SO2, NOx, 03, CO, non-methane hydrocarbon （NMHC） and ambient particle number concentrations as well as modeled photolysis frequencies obtained from measurements. The maximum midday sulphuric acid concentrations vary from 4.53 × 10^7 to 2.17 × 10^8 molecules cm^-3, the corresponding source rate via reaction of OH and SO2 range between 2.37 × 10^6 and 1.16 × 10^7 molecules cm^-3 s^-1. Nucleation mode growth rate was derived from size spectral evolution during the events to be 6.8-13.8 nm h^-1. Based on the growth rate, concentration of the vapors participating in subsequent growth were estimated to vary from 1.32 × 10^8 to 2.80 × 10^8 molecules cm^-3 with corresponding source rate between 7.26 × 10^6 and 1.64 × 10^7 molecules cm^-3 s^-1. Our results show the degree of pollution is larger in PRD. Sulphuric acid concentrations are fairly high and have a close correlation with new particle formation events. Budget analysis shows that sulphuric acid alone is not enough for required growth; other nonvolatile vapors are needed. However, sulphuric acid plays an important role in growth; the contribution of sulphuric acid to growth in PRD is 12.4%-65.2%.